Modern trends in financial instruments in Ukraine - Shyshkov, Stanislav; Shyshkova, Nataliia (My University, 2015)
Abstract. The article deals with the problem of evaluation methodology and accounting of financial instruments. A systematize the accounting policies of enterprises in financial instruments for the purposes of financial and tax reporting and providing information bases - management entity. Pull something and reasonable hypothesis about the possibility of using marketing methods exchange rate. Suggestions on the economic feasibility of implementing internal control operations with de-rivatives.
Keywords: Keywords: exchange rate; financial markets; exchange trading; market methods of regulation; hedging; accounting.